Synthesis, structural and electrochemical properties of Ni-rich material prepared by a sol-gel method - Tung, Mai Thanh; Luong, Vu Duc (Vietnam Journal of Chemistry, 2016)
We report on a novel synthetic method of sol-gel processing to prepare Ni-rich cathode materials. We also studied and reported on the electrochemical properties of the resultant products. XRD revealed that a single phase Ni-rich powder can be synthesized by sol-gel processing. The Ni-rich material obtained has a high electrochemical capacity and good cycle ability. These results indicate that sol-gel processing is a promising method for preparing Ni-rich cathode materials. The sample prepared under the optimal conditions had a well ordered hexagonal layered structure. The charge–discharge tests showed that the initial capacities of the sample were 220.456 and 185.937 mAhg-1at the discharge rate of 0.1 C between 3.0 and 4.3 V, respectively. The capacity retention ratio was 81.36 % at 1 C after 50 cycles.